2005
DOI: 10.1345/aph.1g271
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation in Alzheimer's Disease, Parkinson's Disease, Tardive Dyskinesia, and Cataract: Part 2

Abstract: We encourage patients to supplement with vitamin E-rich foods. The use of a daily multivitamin, which usually contains 30 IU of alpha-tocopherol, may be beneficial; however, we discourage individual vitamin E supplements that usually contain 400 IU of alpha-tocopherol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 68 publications
1
38
0
1
Order By: Relevance
“…Dose dependent supplementation of vitamin E could offer the neuroprotective effects in AD and PD. Pham and Plakogiannis (2005) [123] have showed that vitamin E enriched food which contains 30IU of α-tocopherol may be beneficial however, they discourage the vitamin E supplement of dose 400IU of α-tocopherol. Dysket et al (2014) [124] showed that mild to moderate AD could be treated with treatment of α-tocopherol.…”
Section: Evidences For the Beneficial Use Of Antioxidants In Neurodegmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose dependent supplementation of vitamin E could offer the neuroprotective effects in AD and PD. Pham and Plakogiannis (2005) [123] have showed that vitamin E enriched food which contains 30IU of α-tocopherol may be beneficial however, they discourage the vitamin E supplement of dose 400IU of α-tocopherol. Dysket et al (2014) [124] showed that mild to moderate AD could be treated with treatment of α-tocopherol.…”
Section: Evidences For the Beneficial Use Of Antioxidants In Neurodegmentioning
confidence: 99%
“…Pham and Plakogiannis (2005) [123] have showed that vitamin E enriched food which contains 30IU of α-tocopherol may be beneficial however, they discourage the vitamin E supplement of dose 400IU of α-tocopherol. Dysket et al (2014) [124] showed that mild to moderate AD could be treated with treatment of α-tocopherol. Recently Morris et al (2015) [125] have suggested that γ-tocopherol might have beneficial effects in AD pathology in comparison to α-tocopherol.…”
Section: Evidences For the Beneficial Use Of Antioxidants In Neurodegmentioning
confidence: 99%
“…However, a number of subsequent prospective randomized placebo-controlled interventional trials have failed to verify a consistent benefit [10][11][12][13][14][15][16][17]. In 1988, the U.S.…”
Section: Health Implications Of Vitamin Ementioning
confidence: 99%
“…At present, there is no substantial evidence that Alzheimer's disease and other forms of dementia such as mild cognitive impairment, as well as Parkinson's disease and other neurodegenerative conditions can be successfully prevented to any extent by the supplementation with vitamin E or other antioxidants [95][96][97][98]. In Alzheimer's disease patients, both preclinical evidence [99,100] and small clinical studies [101] suggested the premise for a therapeutic perspective that needs, however, further substantiation.…”
Section: Neurodegenerative and Other Neurological Conditionsmentioning
confidence: 99%
“…In Alzheimer's disease patients, both preclinical evidence [99,100] and small clinical studies [101] suggested the premise for a therapeutic perspective that needs, however, further substantiation. Idiopathic neurological disorders associated with symptoms resembling those of AVED should be further investigated at the clinical level and could be considered at least in certain cases for a symptomatic first-approach treatment with vitamin E. These may include some forms of inherited ataxias [102], and patients with tardive dyskinesia have been proposed as candidate population that may benefit of such a prophylactic treatment [96]. Some symptoms in rare neurodegenerative conditions such as familial dysautonomia seem to be positively affected by tocotrienol supplementation [103], and vitamin E supplementation is recommended in secondary neurological disturbance that may rise over the long-term as a consequence of vitamin E deficiency in gastrectomy patients [104].…”
Section: Neurodegenerative and Other Neurological Conditionsmentioning
confidence: 99%